Linguistic Variation in the Acquisition of Morphosyntax: Variable Object Marking in the Speech of Mexican Children and Their Caregivers. Issue 3 (3rd July 2022) - Callen, M. Cole; Miller, Karen
ABSTRACT: Research in language development has only recently begun to focus on the inherent variability of language. Previous studies have explored at what age children begin to produce variable linguistic forms and how these forms progress through development. While children produce adult-like variation early on, some variable forms take longer to acquire than others do. The current study builds on this previous research using naturalistic corpus data to compare variable differential object marking in the speech of Spanish-speaking children and their caregivers. While previous studies of adult speech have highlighted the variable use of the accusative object marker a, the variable distribution of the a- marker has been largely overlooked in studies of child Spanish. Our results show that preschool-age children use the same linguistic constraints as their caregivers when producing direct objects. We also found that younger children show different patterns of a- marking compared to older children and caregivers. These patterns suggest that the developmental trajectory of individual linguistic constraints depends on the distribution of variable contexts in the child's input. Our findings highlight the importance of examining caregivers' use of variable forms alongside children's productions in language acquisition research.